2019
DOI: 10.28932/jmm.v18i2.1611
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Fundamental and Technical Analysis in Predicting the Stock Price

Abstract: Fundamental Analysis and Technical Analysis have long been used by investors as an analysis instrument to predict the stock price in gaining optimal return. The purpose of this study is to test the predictive ability of Fundamental Analysis and Technical Analysis  model partially, then simultaneously test the integrated model of both analysis. The scope of this study includes the listed companies in LQ 45 stock exchange during 2007- 2016 period. The Fundamental Variable used in this study are Earning per Share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 4 publications
0
9
0
4
Order By: Relevance
“…Kengatharan (2018) revealed that the earnings per share, dividend per share and size of the bank have significantly affected the share prices of local banks listed in Sri Lanka. Agustin (2019) found that there is a positive impact of the earnings per share on fluctuations in share prices, while there is a negative and not statistically significant effect of the dividend payout ratio on the share price.…”
Section: Theoretical Backgroundmentioning
confidence: 92%
“…Kengatharan (2018) revealed that the earnings per share, dividend per share and size of the bank have significantly affected the share prices of local banks listed in Sri Lanka. Agustin (2019) found that there is a positive impact of the earnings per share on fluctuations in share prices, while there is a negative and not statistically significant effect of the dividend payout ratio on the share price.…”
Section: Theoretical Backgroundmentioning
confidence: 92%
“…Fuzzy classification helps investors to make better and faster selection of stocks in the Stock Exchange market considering their capital and the risk of stocks [11,32]. This choice is made using technical or fundamental analysis [1,34,44]. There are many analytical approaches for decision making in stock market, which are categorized in two groups: technical analysis and fundamental analysis [8,34].…”
Section: Introductionmentioning
confidence: 99%
“…This method is applicable to stocks, indices or commodities in which the price is influenced by the forces of supply and demand. In fact, technical analysis tries to predict future prices using iterative patterns such as recurring and continuing movements as well as indicators [1,34,44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dalam pasar modal tidak diragukan akan terdapat risiko kerugian, dimana dapat diminimalisir dengan melakukan analisis fundamental (Agustin, 2019). Analisis ini menjadi dasar yang sangat penting dalam melakukan investasi guna menghindari kerugian serta mendapatkan profit secara maksimal (Ramlah, 2021).…”
unclassified